The Effect of Synovial Fluid Composition, Speed and Load on Frictional Behaviour of Articular Cartilage - Furmann, Denis; Nečas, David; Rebenda, David; Čípek, Pavel; Vrbka, Martin; Křupka, Ivan; Hartl, Martin (Materials (Basel, Switzerland), 2020)
Articular cartilage ensures smooth motion of natural synovial joints operating at very low friction. However, the number of patients suffering from joint diseases, usually associated with cartilage degradation, continuously increases. Therefore, an understanding of cartilage tribological behaviour is of great interest in order to minimize its degradation, preserving the reliable function of the joints. The aim of the present study is to provide a comprehensive comparison of frictional behaviour of articular cartilage, focusing on the effect of synovial fluid composition (i), speed (ii), and load (iii). The experiments were realized using a pin-on-plate tribometer with reciprocating motion. The articular cartilage pin was loaded against smooth glass plate while the tests consisted of loading and unloading phases in order to enable cartilage rehydration. Various model fluids containing albumin, γ-globulin, hyaluronic acid, and phospholipids were prepared in two different concentrations simulating physiologic and osteoarthritic synovial fluid. Two different speeds, 5 mm/s and 10 mm/s were applied, and the tests were carried out under 5 N and 10 N. It was found that protein-based solutions exhibit almost no difference in friction coefficient, independently of the concentration of the constituents. However, the behaviour is considerably changed when adding hyaluronic acid and phospholipids. Especially when interacting with γ-globulin, friction coefficient decreased substantially. In general, an important role of the interaction of fluid constituents was observed. On the other hand, a limited effect of speed was detected for most of the model fluids. Finally, it was shown that elevated load leads to lower friction, which corresponds well with previous observations. Further study should concentrate on specific explored phenomena focusing on the detailed statistical evaluation.
Keywords: biotribology; tribological properties; synovial fluid; articular cartilage; coefficient of friction